Growth and yield components of wheat genotypes exposed to high temperature stress under control environment - Rahman, M Ataur; Chikushi, Jiro; Yoshida, Satoshi; Karim, AJMS (Bangladesh Journal of Agricultural Research, 2009)
High temperature stress during grain-filling period is one of the major environmental constraints limiting the grain yield of wheat in Bangladesh. Crop growth response and relative performance of yield components of ten wheat genotypes were studied in two temperature conditions in glass rooms in a Phytotron to identify the genotype tolerant to high temperature stress. A favourable day/night temperatures of 15/10, 20/15, and 25/20°C were maintained from sowing to 60 days after sowing (DAS), 61 to 80 DAS and 81 DAS to maturity, respectively, in one glass room (G1); whereas day/night temperatures in another glass room (G2) was always maintained at 5°C higher than that of G1. Green leaf area and number of tillers in different times, number of days for the occurrence of major crop growth stages, relative performance in yield components, grain yield and heat susceptibility index were estimated following the standard methods. The higher temperature enhanced plant growth, flowering, and maturation. Thus the number of days to booting, heading, anthesis, and maturity of wheat were significantly decreased that varied among the genotypes. Green leaf area and productive tillers/plant were drastically reduced in time under high temperature. The reduced number of grains/spike and smaller grain size resulted from drastic reduction in growth duration were responsible for the yield loss of wheat at high temperature. Out of ten wheat genotypes, three were characterized as high temperature tolerant based on their relative performance in yield components, grain yield and heat susceptibility index. Key Words: High-temperature tolerance, wheat genotype, growth and yield components. DOI: 10.3329/bjar.v34i3.3961 Bangladesh J. Agril. Res. 34(3) : 361-372, September 2009